A proposed audio-visual program for the Mindanao Institute of Technology - Pableo, Librada C. (1970)
The purpose of the study is to propose an audio-visual program for the Mindanao Institute of Technology. It looked into the practices and trends in the organization, establishment and administration, and the principles common to a college audio-visual program.
Thesis (M.Ed.)--University of the Philippines, Diliman.
Keywords: Mindanao Institute of Technology, Cotabato; Teaching -- Aids and devices